The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/healthcare10040594
|View full text |Cite
|
Sign up to set email alerts
|

External Match Load in Amateur Soccer: The Influence of Match Location and Championship Phase

Abstract: Assessment of the physical dimension implicit in the soccer match is crucial for the improvement and individualization of training load management. This study aims to: (a) describe the external match load at the amateur level, (b) analyze the differences between playing positions, (c) verify whether the home/away matches and if (d) the phase (first or second) of the championship influence the external load. Twenty amateur soccer players (21.5 ± 1.9 years) were monitored using the global positioning system. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 57 publications
2
13
2
Order By: Relevance
“…Moreover, wide defenders and wide midfielders perform the highest sprinting distance, whereas central midfielders and central backs cover the lowest in elite soccer players [21][22][23][24][25]. Moreover, significant differences were found between the various playing positions for all measures of EL in amateur soccer players [26]. Authors reported that central midfielders covered the longest distance during a match, which is in line with recent literature followed by the forwards, the full-backs, and the wide midfielders.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Moreover, wide defenders and wide midfielders perform the highest sprinting distance, whereas central midfielders and central backs cover the lowest in elite soccer players [21][22][23][24][25]. Moreover, significant differences were found between the various playing positions for all measures of EL in amateur soccer players [26]. Authors reported that central midfielders covered the longest distance during a match, which is in line with recent literature followed by the forwards, the full-backs, and the wide midfielders.…”
Section: Introductionsupporting
confidence: 81%
“…In our study, significant differences in cinematic EL indicators between playing positions during the first half time of an OM were detected. Several previous studies have found differences in EL as distance, speed, and accelerations [38][39][40] between playing positions during both training and competition including both elite and amateur soccer players [26]. Moreover, considering physiological characteristics (i.e., HR and derived indices) [41,42] similar results have been found.…”
Section: Cinematic External Load Indicatorssupporting
confidence: 71%
“…However, match running can be influenced by seasonal variations that need to be quantified in order to model individual and collective performance [5,6]. Several studies were published demonstrating the measurement of the match load in regional [7,8], national [4,9,10], and international competitions [11,12], reporting specific seasonal variation in match running for each competition. However, only three studies were carried out in Portuguese professional, semi-professional, and amateur football leagues [7,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies were published demonstrating the measurement of the match load in regional [7,8], national [4,9,10], and international competitions [11,12], reporting specific seasonal variation in match running for each competition. However, only three studies were carried out in Portuguese professional, semi-professional, and amateur football leagues [7,9,10]. It is therefore important to study the Portuguese league, which is in the top 10 best European leagues and recurrently in the UEFA top-five ranking [13].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, one study was a systematic review that summarized studies about external and internal training load monitoring to provide range values for the main measures in young male soccer players [ 13 ]. Another study compared the external load between official and friendly matches and between the first and second halves of professional soccer players [ 14 ], while another analyzed differences among playing positions: whether playing home/away matches and if playing in the first or second part of the championship influence the external load of amateur soccer [ 15 ]. Moreover, external load was compared between starters and non-starters [ 16 ] and among the playing positions [ 17 ] of professional soccer players based on different parts of a full season.…”
mentioning
confidence: 99%